Free Revascularized Fibula Graft for Reconstruction of Mandibular Continuity Defects - Rahman, QB; Karmakar, R; Aftabuddin, M (Bangladesh Medical Journal, 2014)
Mandibular reconstruction represents a challenge to the oral and maxillofacial surgeon and has been revolutionized by the modern microvascular techniques Objective: To evaluate the usefulness of the free vascularized fibula graft for reconstruction of discontinuity defects of Mandible after resections of benign aggressive odontogenic tumours. The results of 7 vascularized free fibula graft without a skin paddle that were used for mandibular reconstruction is presented. The "double barrel" technique was used in 1 case. The donor site was closed directly in all cases. All procedures were performed by the same surgical team in oral and Maxillofacial Surgery department of BSMMU and Health & Hope Hospital from January, 2006 to December 2011. A total of patients (3 males, 4 females) were treated. All flaps except 1 were viable. Success rate was 85.71% .The average length of the fibula graft was 10.96 cm, and the number of osteotomies ranged from 0 to 3. There were no long-term functional complications in the lower leg. The fibula flap provides a successful bone graft for mandibular restoration with an acceptably low complication rate. DOI: http://dx.doi.org/10.3329/bmj.v41i1.18782 Bangladesh Medical Journal 2012 Vol. 41 No. 1; 45-49